2019
DOI: 10.3389/fgene.2019.00424
|View full text |Cite
|
Sign up to set email alerts
|

Germline Risk Contribution to Genomic Instability in Multiple Myeloma

Abstract: Genomic instability, a well-established hallmark of human cancer, is also a driving force in the natural history of multiple myeloma (MM) – a difficult to treat and in most cases fatal neoplasm of immunoglobulin producing plasma cells that reside in the hematopoietic bone marrow. Long recognized manifestations of genomic instability in myeloma at the cytogenetic level include abnormal chromosome numbers (aneuploidy) caused by trisomy of odd-numbered chromosomes; recurrent oncogene-activating chromosomal transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 180 publications
2
13
0
Order By: Relevance
“…Consistent with recent findings in breast cancer 37 , in our series, SV hotspots showed seven-fold enrichment for multiple myeloma germline predisposition SNPs as compared with the remaining mappable genome (6 SNPs in 125 Mb of hotspots vs 17 in the remaining genome, Poisson test p = 0.0002; Figure S6 ) 48,49 . The involved SNPs were on 3q26.2 (SV hotspot involving SEC62/SAMD7 ), 6p21.3 (unknown SV target), 6q21 ( ATG5/PRDM1 ), 9p21.3 ( CDKN2A/CDKN2B ), 19p13.11 ( KLF2 ) and 2q31.1 ( SP3 ) ( Table S8 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with recent findings in breast cancer 37 , in our series, SV hotspots showed seven-fold enrichment for multiple myeloma germline predisposition SNPs as compared with the remaining mappable genome (6 SNPs in 125 Mb of hotspots vs 17 in the remaining genome, Poisson test p = 0.0002; Figure S6 ) 48,49 . The involved SNPs were on 3q26.2 (SV hotspot involving SEC62/SAMD7 ), 6p21.3 (unknown SV target), 6q21 ( ATG5/PRDM1 ), 9p21.3 ( CDKN2A/CDKN2B ), 19p13.11 ( KLF2 ) and 2q31.1 ( SP3 ) ( Table S8 ).…”
Section: Resultssupporting
confidence: 91%
“…Germline predisposition SNPs for multiple myeloma were obtained from a recent meta-analysis of GWAS-studies 48,49 . Poisson test for enrichment in hotspots was performed as for super-enhancers.…”
Section: Methodsmentioning
confidence: 99%
“…The mutational landscape analyses demonstrated that more patients with high TMB were in the phase two cohort compared to phase one. This finding is consistent with greater tumor genomic instability in a more heavily pre‐treated R/R MM population 36,37 . Similarly, more patients with del(17p) and gain(1q) were in the phase two cohort compared to phase one.…”
Section: Discussionsupporting
confidence: 73%
“…Genomic instability, a hallmark of all neoplastic diseases, is the source of genetic heterogeneity of MM not only at the individual patient level (intrapatient genetic heterogeneity), but also between patients with the same diagnosis (interpatient heterogeneity) [35,70,71]. Therefore, the molecular landscape of newly diagnosed MM is heterogeneous as there is no universal mutation pattern typical for MM [16][17][18][19][72][73][74].…”
Section: Genomic Landscape Of Multiple Myelomamentioning
confidence: 99%